Mycoplasma infection promotes tumor progression via interaction of the mycoplasmal protein p37 and epithelial cell adhesion molecule in hepatocellular carcinoma. (10th July 2019) - Kim, Min Kyu; Shin, Su-Jin; Lee, Hyun Min; Choi, Hong Seo; Jeong, Jaemin; Kim, Hyunsung; Paik, Seung Sam; Kim, Mimi; Choi, Dongho; Ryu, Chun Jeih
Abstract: Hepatocellular carcinoma (HCC) is currently the third leading cause of cancer death worldwide. To study how mycoplasma infection affects HCC progression, we investigated the characteristics of mycoplasma-infected tumor tissues and circulating tumor cells (CTCs) in HCC patients. The mycoplasmal membrane protein p37 showed significant correlations with higher histologic stages and vascular invasion and predicted poor disease-free survival of HCC patients. p37-positive CTCs were detected in 42 out of 47 HCC patients (89%). p37-positive circulating cells were also detected in 4 out of 10 healthy donors (40%), and all were epithelial cell adhesion molecule (EpCAM)-positive. In HCC patients, most of p37-negative CTCs (95%) showed intermediate phenotype with neither EpCAM nor vimentin expression, but p37-positive CTCs were EpCAM-positive (44%), vimentin-positive (32%), and both negative (24%), suggesting that EpCAM-positive CTCs are enriched with mycoplasma infection. Mycoplasma infection promoted migratory capacity of HCC cells with increased expression of EpCAM. Immunoprecipitation analysis revealed that p37 associates with EpCAM. The results suggest that mycoplasma infection promotes tumor progression in HCC patients via interaction of the mycoplasmal p37 and EpCAM. Highlights: Mycoplasmal protein p37 associates with poor disease-free survival in HCC patients. p37-positive CTCs show EpCAM- or vimentin-positive phenotype. Mycoplasma infection promotes HCC cell migration with increased expression of EpCAM. p37 physically interacts with EpCAM. Mycoplasma infection promotes HCC progression via interaction of p37 and EpCAM.